2018
DOI: 10.4236/ojapps.2018.811039
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Drunk Driving Traffic Accidents Based on Logistic Regression Model

Abstract: Most of the current studies on drunk driving accidents focus on law making and public education. However, especially in China, there is less statistical analysis on the severity of drunk driving accidents between driving under the influence of alcohol (DUI) and driving while intoxicated (DWI). 3368 drunk driving related crashes were collected from the blood-alcohol test report in a city of China at 2012 and 2013. After data pre-processing, Chi-square tests were used to analyze the association between different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Of those who reported drinking and driving, 76.5% indicated they 'felt conscious enough' to drive at the time and 34.0% reported having 'no other available transportation options'. Similarly, Wang et al, (2018) found out that hour of the day, driver's age, driver's casualties and accident area have significant correlation with drunk driving. However, there was a slightly decrease by 0.995 per year with age and a slightly increase by 1.014 with time in the possibility of driving while intoxicated (DWI -which could mean that a driver has an alcohol content above the legal limit and she/ he is impaired while driving).…”
Section: Drinking and Traffic Injuriesmentioning
confidence: 86%
See 1 more Smart Citation
“…Of those who reported drinking and driving, 76.5% indicated they 'felt conscious enough' to drive at the time and 34.0% reported having 'no other available transportation options'. Similarly, Wang et al, (2018) found out that hour of the day, driver's age, driver's casualties and accident area have significant correlation with drunk driving. However, there was a slightly decrease by 0.995 per year with age and a slightly increase by 1.014 with time in the possibility of driving while intoxicated (DWI -which could mean that a driver has an alcohol content above the legal limit and she/ he is impaired while driving).…”
Section: Drinking and Traffic Injuriesmentioning
confidence: 86%
“…Compared with casualties aged between 30 and 59 years, children under 10 years and the aged (60 years and above) were independently, two times more likely to die in traffic collisions. Consequently, the unanimous consensus among researchers (Bachani et al, 2016;Damsere-Derry et al, 2017& Wang et al, 2018 is on the need for social marketing, public education campaigns, enhanced enforcement, and programmes that either limit the number of drinks to drivers or provide alternatives to drinking and driving.…”
Section: Drinking and Traffic Injuriesmentioning
confidence: 99%
“…15,16 Driver deaths are more likely to occur than injuries when a driver is found to have drunk and driven. 17 In a study in the Philippines by Marquez et al 18 , alcohol is one factor for sustaining severe injuries in road crashes since alcohol impairs normal function of the brain and central nervous system, thus, adversely affecting decision making and alertness. 19 Alcohol affects motor skills of the eye, hand, and foot coordination.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [23] researched the differences between driving under the influence of alcohol (DUI) and driving while intoxicated (DWI) in China. e results showed that the blood alcohol concentration was between 0.02 mg/l and 0.08 mg/l for DUI offenders and higher than 0.08 mg/l for DWI offenders.…”
Section: Literature Reviewmentioning
confidence: 99%